2023
DOI: 10.1094/pbiomes-02-22-0008-fi
|View full text |Cite
|
Sign up to set email alerts
|

Metagenomic Next-Generation Sequencing (mNGS) Data Reveal the Phyllosphere Microbiome of Wheat Plants Infected by the Fungal PathogenZymoseptoria tritici

Abstract: The fungal pathogen Zymoseptoria tritici is the causal agent of Septoria tritici blotch (STB), a major wheat disease in Western Europe. Microorganisms inhabiting wheat leaves might act as beneficial, biocontrol or facilitating agents that could limit or stimulate the development of Z. tritici. Improving our understanding of microbial communities in the wheat phyllosphere would lead to new insights into STB management. This resource announcement provides fungal and bacterial metabarcoding datasets obtained by s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…One of the pioneering studies in fungal pathogen detection studies identified the microbiome of plants infected by Zymoseptoria tritici in wheat plants [51]. The result, obtained in this study using 450 leaf samples, shows significant differences in the microbiota of healthy tissue and infected tissue.…”
Section: Algorithm Tools Referencesmentioning
confidence: 57%
“…One of the pioneering studies in fungal pathogen detection studies identified the microbiome of plants infected by Zymoseptoria tritici in wheat plants [51]. The result, obtained in this study using 450 leaf samples, shows significant differences in the microbiota of healthy tissue and infected tissue.…”
Section: Algorithm Tools Referencesmentioning
confidence: 57%
“…One of the pioneering studies in fungal pathogenicity determination studies is the study aiming to determine the microbiome of plants infected by Zymoseptoria tritici fungus, one of the common diseases of wheat plants [36]. The result obtained in this study using 450 leaf samples shows significant differences between healthy tissue and infected tissue microbiota.…”
Section: Successful Applications Of Mngs To Detect Fungal Plant Patho...mentioning
confidence: 77%
“…Z. tritici is a major fungal pathogen of wheat, causing the economically important foliar disease Septoria tritici blotch (STB) ( 28 ). The pathogen constitutes an important component of the microbiome associated with wheat plants ( 29 ). Z. tritici is thought to overwinter in the soil as spores or mycelium ( 30 ).…”
Section: Introductionmentioning
confidence: 99%